2023
DOI: 10.1007/s11356-023-26288-8
|View full text |Cite
|
Sign up to set email alerts
|

A review on natural based deep eutectic solvents (NADESs): fundamentals and potential applications in removing heavy metals from soil

Abstract: Natural based deep eutectic solvent (NADES) is a promising green solvent to replace the conventional soil washing solvent due to the environmental benign properties such as low toxicity, high biodegradability, high polarity or hydrophilicity, and low cost of fabrication process. The application of NADES is intensively studied in the extraction of organic compounds or natural products from vegetations or organic matters. Conversely, the use of the solvent in removing heavy metals from soil is severely lacking. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 92 publications
0
1
0
Order By: Relevance
“…The authors concluded that the chosen NADES were non-toxic and safe for further utilization. The detailed mechanism of binding NADES to heavy metals was explained in the paper by Lai et al [ 33 ]. In addition to the proven fact that lactic acid has the ability to bind metals, it is necessary to emphasize the need to establish appropriate conditions, such as the solid–liquid ratio, contact time, and concentration.…”
Section: Resultsmentioning
confidence: 99%
“…The authors concluded that the chosen NADES were non-toxic and safe for further utilization. The detailed mechanism of binding NADES to heavy metals was explained in the paper by Lai et al [ 33 ]. In addition to the proven fact that lactic acid has the ability to bind metals, it is necessary to emphasize the need to establish appropriate conditions, such as the solid–liquid ratio, contact time, and concentration.…”
Section: Resultsmentioning
confidence: 99%